Sectorial Perceptions of Parental Involvement: Similarities and Dissimilarities - Fisher, Yael (Advances in Social Sciences Research Journal, 2014)
The study examined the perceptions of parental involvement among 320 Arab-sector- and 319 Jewish-sector elementary-school teachers in Israel. On a questionnaire listing potential components of the concept, participants indicated the degree of pertinence of each. Findings showed that teachers in both sectors agreed that parental involvement includes three components: pedagogy, control, and resources. Both sectors identified the three most significant parental activities as related to the hiring and firing of teachers, understanding classroom social dynamics, and fundraising for extracurricular activities. A cross-sector conceptualization of the term parental involvement creates a shared language and facilitates public discourse on educational issues. Key words: Parental Involvement; Elementary schools; Teachers' perceptions